A case study on geogrid-reinforced and pile-supported widened highway embankment. Issue 3 (18th June 2020) - Lu, W.; Miao, L.; Wang, F.; Zhang, J.; Zhang, Y.; Wang, H.
Abstract : The objective of this case study is to evaluate the development of soil arching in an embankment being widened. In two test sections, earth pressures at different locations were monitored to reveal the load redistribution mechanism due to soil arching. Tensile forces in uniaxial plastic geogrids were measured to evaluate the performance of geosynthetic reinforcement in the widened embankment. The soil arching effect was quantified in terms of stress concentration ratio, soil arching ratio and geomembrane effect. Several existing methods were selected to compare with the measured results. The results of the field tests indicate that a two-dimensional plane soil arch with some eccentricity affects the fill load distribution on pile caps and subsoil between piles, and a realistic critical arch height of less than 2.0 m with a ratio of 1.4 times the pile clear spacing was identified. Although few existing methods could generate close results comparable to the measured values, most of the methods overestimated the load carried by the geosynthetic layer. The results also suggest that the foundation soil reaction underneath the geosynthetic layer should be taken into account in the load transfer mechanism of geosynthetic-reinforced and pile-supported widened highway embankments.